2020
DOI: 10.1001/jamasurg.2020.3021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Autonomy in Operative Procedures Among Female and Male New Zealand General Surgery Trainees

Abstract: examining all endoscopic, major, and minor procedures performed by all New Zealand general surgery trainees in every training hospital in New Zealand. MAIN OUTCOMES AND MEASURESThe primary outcome was the level of meaningful autonomy by each New Zealand general surgery trainee (ie, trainee as primary operator without the surgeon mentor scrubbed for the case). Outcomes were compared using multivariable analysis. RESULTSThis study included 120 New Zealand general surgery trainees (42 women [35%] and 78 men [65%]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…Within surgery, a 2020 study found that trainee gender did not impact evaluations of meaningful autonomy in the operating room ( 14 ). In contrast, other studies have reported lower autonomy among women surgical trainees ( 15 , 16 ). Whether gender differences are detected may also depend on the type of competencies being assessed as well as the timing of these evaluations.…”
Section: Discussioncontrasting
confidence: 60%
“…Within surgery, a 2020 study found that trainee gender did not impact evaluations of meaningful autonomy in the operating room ( 14 ). In contrast, other studies have reported lower autonomy among women surgical trainees ( 15 , 16 ). Whether gender differences are detected may also depend on the type of competencies being assessed as well as the timing of these evaluations.…”
Section: Discussioncontrasting
confidence: 60%
“… 21 A 2019 study found that female general surgery residents in the USA were significantly less likely to be granted operative autonomy by faculty than men, 7 similar findings were seen among New Zealand general surgery trainees. 22 The finding that women across all specialties have adverse outcomes requires investigation at the specialty level.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis comprising 17,407 surgical trainees across the world, women were found to have a higher pooled attrition than men[20]. A 2019 study found that female general surgery residents in the US were significantly less likely to be granted operative autonomy by faculty than men[6], similar findings were seen amongst New Zealand general surgery trainees[21]. The finding that women across all specialities have adverse outcomes requires investigation at the specialty level.…”
Section: Discussionmentioning
confidence: 99%